Lack of whey acidic protein (WAP) four-disulfide core domain protease inhibitor 2 (WFDC2) causes neonatal death from respiratory failure in mice - Kuniko Nakajima; Michio Ono; Uroš Radović; Selma Dizdarević; Shin-ichi Tomizawa; Kazushige Kuroha; Go Nagamatsu; Ikue Hoshi; Risa Matsunaga; Takayuki Shirakawa; Takeyuki Kurosawa; Yasunari Miyazaki; et al. (The Company of Biologists, 2019)
Respiratory failure is a life-threatening problem for pre-term and term infants, yet many causes remain unknown. Here, we present evidence that whey acidic protein (WAP) four-disulfide core domain protease inhibitor 2 (Wfdc2), a protease inhibitor previously unrecognized in respiratory disease, may be a causal factor in infant respiratory failure. Wfdc2 transcripts are detected in the embryonic lung and analysis of a Wfdc2-GFP knock-in mouse line shows that both basal and club cells, and type II alveolar epithelial cells (AECIIs), express Wfdc2 neonatally. Wfdc2-null-mutant mice display progressive atelectasis after birth with a lethal phenotype. Mutant lungs have multiple defects, including impaired cilia and the absence of mature club cells from the tracheo-bronchial airways, and malformed lamellar bodies in AECIIs. RNA sequencing shows significant activation of a pro-inflammatory pathway, but with low-quantity infiltration of mononuclear cells in the lung. These data demonstrate that Wfdc2 function is vitally important for lung aeration at birth and that gene deficiency likely causes failure of the lung mucosal barrier.